Edukasi dengan Media Video tentang ASI Eksklusif Melalui Aplikasi Whatsapp Meningkatkan Pengetahuan dan Sikap Ibu Menyusui - Wibowo, Abdilla Fi Qisthy; Kuswati, Kuswati; Istikhomah, Henik (Poltekkes Kemenkes Surakarta, 2023)
Background: Low rates of exclusive breastfeeding in Indonesia remain a public health issue due to mothers' lack of knowledge and positive attitudes towards the benefits of exclusive breastfeeding. Based on initial observations in the working area of the Banyuanyar Surakarta Community Health Centre, many mothers are still not breastfeeding exclusively as recommended by the WHO. This community service activity aims to increase breastfeeding mothers' knowledge and attitudes about the importance of exclusive breastfeeding through education using video media delivered via the WhatsApp application. Methods: The partners in this activity were breastfeeding mothers in the working area of the Banyuanyar Surakarta Community Health Centre, with a total of 45 participants. The activity was carried out in three stages, namely programme socialisation, video-based education, and interactive discussions through a WhatsApp group. The educational material covered the definition of exclusive breastfeeding, its benefits for mothers and babies, proper breastfeeding techniques, and how to maintain milk production. Evaluation was conducted using questionnaires before and after the activity to assess the increase in knowledge and attitudes of breastfeeding mothers. Results: The results of the activity showed an increase in participants' knowledge of 40.3%, from an average score of 13.78 to 19.33, as well as an increase in positive attitudes towards exclusive breastfeeding of 25.7%, from an average score of 54.47 to 68.51. Conclusion: This activity proves that education through video media via WhatsApp is effective in improving the soft skills and awareness of breastfeeding mothers about exclusive breastfeeding. This programme can be used as a model for efficient and easily implemented digital-based health education at the primary care level.